“Thresholds in the Poetry of Saad Ali Mahdi: The Collection ‘I Still Dream of Dew’ as a Model” - Aziz, Ass. Alaa Ahmed (Thi Qar Arts Journal, 2024)
Thresholds are keys that enable the reader to open the gates of the text, decipher its codes, and extract its connotations to get rid of the ambiguity that plagues the text. Hence, this study, entitled (Thresholds in the Poetry of Saad Ali Mahdi Diwan, I Still Dream of Dew as an Example), seeks to identify the external and internal thresholds from which the Diwan was composed. We rely on the semiotic approach to study these thresholds